Secondary school principals' perceptions and experience of management development programmes - Madasi, Vuyelwa (Rhodes University, Faculty of Education, Department of Education, 2005)
Management development in educational contexts is a relatively recent development in South Africa. The Task Team Report on Education Management Development of 1996 drew pertinent attention to the need for education management development in South Africa, and set an agenda for such development. Since then many management development programmes have been launched by both National and Provincial government. However, very little research seems to have been conducted on these programmes, especially on how they have been received. This study seeks to address that need. The study is a qualitative phenomenological investigation of how four secondary school principals experienced and perceived the management development programmes they have attended. In line with a phenomenological approach, the study sets aside preconceived ideas and attempts to describe the phenomenon through the eyes of the participants. Findings suggest that management development programmes are perceived as having a big role to play in the development of school managers, but that the programmes on offer suffer from various shortcomings. These include poor planning, lack of organisational and facilitating skills in presenters, lack of commitment, monitoring and support from the bodies offering the courses, and especially the failure of training programmes to bring about increased confidence and self-awareness among participants. Increased selfawareness can help in personal and organisational renewal and growth, and help to minimise the dependency syndrome among principals. Particular needs highlighted by the findings include training in the new curriculum (Outcomes Based Education), holistic development by experts in all facets of school management, training of School Governing Bodies and development of all educators in management as future managers. These findings may prove helpful to education departments and other bodies in the planning and delivery of programmes for new and incumbent school managers.
Keywords: Educational change -- South Africa; School management and organization -- South Africa; Educational leadership -- South Africa; Educational planning -- South Africa; School improvement programs -- South Africa